The human mRNA decay machinery : an unexpected role for DIS3L2 over nonsense-mediated decay targets - Costa, Paulo Jorge Gomes Pereira da, 1987- (2021)
Tese de doutoramento, Biologia (Biologia de Sistemas), Universidade de Lisboa, Faculdade de Ciências, 2018